Nederlandse Interpersoonlijke Pragmatic Markers: Syntactische verschillen van hoor, kijk, luister, weet je en zeg in het Nederlandse Nederlands en in het Vlaamse Nederlands - Tóth, Dóra (FILOGI, 2025)
Pragmatic markers (PMs), based on their functions, are generally separated into textual and interpersonal categories. Textual PMs help to organise the discourse, while interpersonal PMs refer to the interaction and its participants. This study examines the differences in the use of the Dutch deverbal interpersonal PMs hoor ‘hear’, kijk ‘look’, luister ‘listen’, weet je/ge ‘you know’ and zeg ‘say’ in two standard varieties of Dutch: Dutch in the Netherlands and Dutch in Belgium. Since the examined words or phrases are deverbal, their syntactic features helped to delineate PMs from their non-PM counterparts. Within the Corpus Gesproken Nederlands (‘Corpus of Spoken Dutch’) I analysed the frequency, function, and place of occurrence of the interpersonal PM in spontaneous, face-to-face conversations. Two main differences were identified. On the one hand, weet je/ge in the Flemish sub-corpus is scarcely used as a PM, which suggests that it is not as grammaticalized in Flanders as it in the Netherlands. On the other hand, based on their place of occurrence, zeg, kijk and luister may fulfil different functions in the two varieties. In Belgian Dutch zeg has two additional functions: zeg at the beginning of questions can attract the hearer’s attention, and as an apart utterance, the speaker can express his/her surprise with it. The additional function of kijk and luister in the Flemish sub-corpus is that they are also used to introduce direct speech.